HUBUNGAN STRATEGI COPING DENGAN PENYESUAIAN DIRI REMAJA DI SMP TAHFIDZ KHAIRUNNAS TUBAN - hanim nur faizah; Hyan Oktodia Basuki; karyo karyo (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2021)
Adaptation in adolescents involves the occurrence of individuals with their ability to be able to accept themselves with the surrounding environment related to how to overcome problems using the coping process. This study aims to look at the use of coping strategies with adjustment in seventh grade adolescents in the Khairunnas Tahfidz Middle School Entrepreneur.This type of research is correlational using a cross sectional time approach with a population of 89 adolescents selected by simple random sampling found 73 adolescents. The independent variable is the coping strategy and the dependent is the adjustment that is measured using the contingency coefficient test.The results of research conducted on seventh grade adolescent Tahfidz Middle School Entrepreneur Khairunnas Tuban after being analyzed using SPSS 23 it is known that the Contingency Coefficient test is ρ = 0,000 and the value of r =0.523 (0.5) means it shows the value of ρ <α (0,000 <0.05) which means that H0 is rejected and H1 is accepted, there is a relationship between coping strategies and adjustment in the seventh grade teenagers of the Tahfidz Middle School Entrepreneur Khairunnas Tuban.From the description above it can be concluded that there is a relationship between coping strategies with adolescent VII grade adolescents in the Tahfidz Middle School Khairunnas Entrepreneur with results based on the Contingency Coefficient Test obtained ρ = 0,000 with a significance level of r = 0.05